Teknik Clustering Dalam Menulis Teks Bahasa Jerman - Melianni Tappang; Syukur Saud; Nurming Saleh (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this study was to determine the increased of German text writing skills from class XI Mipa SMAN 8 Makassar through clustering technique. This type of study was class action study consisting of two cycles with. Each cycle consists of twice the meeting. The subject of this was the class XI Mipa 6th SMAN 8 Makassar. This type of research data exists two, namely Qualitative data and quantitave data. Qualitative data is obtained from the results of teacher and student observation, while quantitative data is obtained from the student writing test. Test results writing student text on the 1st cycle was obtained an average of 66,44 and experiencing an increase in the 2nd cycle with an average value of 81,24. The results of this study indicate that the application of clustering technique can impove the skill of writing German text by class XI Mipa SMAN 8 Makassar.